Cytonemes extend their reach - Kornberg, Thomas B (European Molecular Biology Organization, 2013)
Nature advance online publication 04 28 2013; doi:; DOI: 10.1038/nature12157 Cytonemes are specialized filopodia, first described in the Drosophila wing imaginal disc, that were proposed to mediate long distance signalling during development. A recent report from Barna and colleagues (Sanders et al, 2013) published in Nature shows that cytonemes in the chick limb bud carry SHH signalling proteins out to signal receiving cells, thus highlighting their evolutionarily conserved roles in cell–cell communication.